Theory of Flame Retardation of Polymeric Materials - Jianjun, Li; Yuxiang, Ou (De Gruyter, 2019)
Flame retardant materials are of vital importance in guaranteeing personal security. Especially the demand for non-toxic, low smoking, polymerized flame retardants increases and new materials enter the market. The authors present the fundamental theory of polymer combustion, compare different flame retardants, describe smoke suppression mechanisms, and explain analyzing techniques for new materials.- Resumé vydavatel
Keywords: polymery; hořlavost; polymers; flammability; elektronické knihy; monografie; electronic books; monographs